The Relation between the Administrative Empowerment and Creative Behavior at Jordanian Private Universities - et. al., Faleh O. Khawaldeh, (Turkish Journal of Computer and Mathematics Education (TURCOMAT), 2021)
The purpose of this study is to identify the relation between the administrative empowerment and creative behavior at Jordanian private universities, the objectives of this study focus on determining the level of administrative innovation in Jordanian private universities from the employee’s perspectives. Further, knowing of the impact of the administrative empowerment on the creative behavior and discrimination in the development of work from workers point of view Jordanian private universities. The study relies on a descriptive analytical method. The questionnaire was designed by researchers, and (150) questionnaires were collected from departments and people in Jordanian private universities. After that, the appropriate statistical analysis was applied, standard deviations, and choose multiple regression. The results showed that the level of application of empowerment and administrative creatively were moderate and showed that same of empowerment in the application level of administrative innovation in all its components. It also showed an effect of years of experience at the level of application of empowerment. The study resulted presenting several recommendations including: strengthening the application of empowerment and activating through appropriate training, and enhancing the ability to take risks, in addition to deploying it and effective means of communication between the employees and the importance of delegation of authority between the administrative levels.